ANALISIS PENGARUH PENGETAHUAN PERPAJAKAN, TARIF PAJAK, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KOTA SEMARANG - Giovany Wibowo; Maryono Maryono (Jurnal Akuntansi dan Pajak, 2023)
Taxes are the largest income in each region which greatly influences the progress of the economy of a country where taxpayer compliance is an obedient and aware attitude of taxpayers in paying and reporting taxes, where the tax is a separate problem in a region. From a sample of 100 people from this study, it was found that knowledge of taxation, tax rates and tax sanctions had a positive and significant influence on taxpayer compliance as well as the results of the test for the coefficient of determination in this study, where the value of the adjusted R Square was 0.522, which means that the variable ability of tax knowledge , tax rates and tax sanctions in explaining the variable of taxpayer compliance amounted to 52.2 percent, the remaining 47.8 percent was explained by other variables outside this study Keywords: knowledge of taxation, tax rates, tax sanctions and taxpayer compliance